Stimulatory responses in α‐ and β‐cells by near‐infrared (810 nm) photobiomodulation. Issue 3 (6th December 2021) - Liebman, Caleb; Loya, Sheccid; Lawrence, Michael; Bashoo, Naziruddin; Cho, Michael
Abstract: Significant efforts have been committed to better understand and regulate insulin secretion as it has direct implications on diabetes. The first phase of biphasic insulin secretion in response to glucose lasts about 10 minutes, followed by a more sustained release persisting several hours. Attenuated insulin release in the first phase is typically associated with abnormal β‐cells. While near‐infrared photobiomodulation (PBM) demonstrates potential for multiple therapeutic applications, photostimulatory effects on α‐ and β‐cells remain to be further elucidated. Herein, we demonstrate that 810 nm PBM exposure at fluence of 9 J/cm 2 can elevate the intracellular reactive oxygen species within 15 minutes following photostimulation. In addition, calcium spiking showed an approximately 3‐fold increase in both ATC1 (α‐cells) and BTC6 (β‐cells) and correlates with hormone secretion in response to PBM stimulation. Our findings could lay a foundation for the development of non‐biologic therapeutics that can augment islet transplantation . Abstract : Could photostimulation be used for potential treatment of diabetes? In this study we demonstrate how the pancreatic cells responsible for stabilizing blood glucose can be modulated by near‐infrared laser stimulation. By facilitating calcium dynamics (images shown), the hormone secreting cells are photonically activated. While additional studies are warranted, our work lays a foundation that non‐biologic phototherapy may be optimally tuned to complement and improve the efficacy of diabetes treatments.